Frequency of causes of pancytopenia in a private hospital in Kathmandu (Health Renaissance, 2013)
Background: Pancytopenia is not a disease entity but a triad of findings that result from a number of disease processes. These disorders may affect bone marrow either primarily or secondarily, resulting in the manifestation of pancytopenia. Objective: To identify the various causes of pancytopenia in patients attending to Star hospital, Kathmandu, Nepal. Methods: Fifty two patients with pancytopenia were included in this study from June 2011 to June 2012. Complete blood count, peripheral blood smear, bone marrow aspiration and trephine biopsies were performed according to standard methods. Results: Out of 52 cases, there were 26 cases(50%) of aplastic anaemia, 18 cases(34.61%) of megaloblastic anaemia, 4 cases(7.69%) of acute leukemia, 2cases(3.84%) of erythroid hyperplasia, 1 case(1.92%) of metastatic tumor and 1 case(1.92%) of multiple myeloma. Conclusion: Aplastic anaemia and megaloblastic anaemia were the most common causes of pancytopenia in this study. Health Renaissance, January-April 2013; Vol. 11 No.1; 134-137 DOI: http://dx.doi.org/10.3126/hren.v11i2.8220